2011
DOI: 10.1098/rsbl.2011.0526
|View full text |Cite
|
Sign up to set email alerts
|

Experimental manipulation of fertility reveals potential lactation costs in a free-ranging marsupial

Abstract: Lactation is the most energetically expensive component of reproduction in mammals. Theory predicts that reproducing females will adjust their behaviour to compensate for increased nutritional demands. However, experimental tests are required, since comparisons of the behaviour of naturally reproducing and nonreproducing females cannot distinguish between true costs of reproduction, individual differences or seasonal variation. We experimentally manipulated reproduction in free-ranging, eastern grey kangaroos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 16 publications
2
26
0
Order By: Relevance
“…The delay in flight could be due to the higher energetic needs of young and mothers (Cripps, Wilson, Elgar, & Coulson, 2011;Gélin, Wilson, Coulson, & Festa-Bianchet, 2013), as these groups might not wish to abandon foraging opportunities until the threat is confirmed to be imminent (Cooper et al, 2003;Stankowich & Blumstein, 2005;Ydenberg & Dill, 1986). This explanation is supported by our finding that resource quality also influenced assessment distance at High Harm sites.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The delay in flight could be due to the higher energetic needs of young and mothers (Cripps, Wilson, Elgar, & Coulson, 2011;Gélin, Wilson, Coulson, & Festa-Bianchet, 2013), as these groups might not wish to abandon foraging opportunities until the threat is confirmed to be imminent (Cooper et al, 2003;Stankowich & Blumstein, 2005;Ydenberg & Dill, 1986). This explanation is supported by our finding that resource quality also influenced assessment distance at High Harm sites.…”
Section: Discussionsupporting
confidence: 64%
“…This finding is contrary to our initial expectations, where we expected that groups with vulnerable individuals would respond quicker to risk in threatening landscapes (Blumstein, ; Cooper & Blumstein, ; Stankowich, ). The delay in flight could be due to the higher energetic needs of young and mothers (Cripps, Wilson, Elgar, & Coulson, ; Gélin, Wilson, Coulson, & Festa‐Bianchet, ), as these groups might not wish to abandon foraging opportunities until the threat is confirmed to be imminent (Cooper et al, ; Stankowich & Blumstein, ; Ydenberg & Dill, ). This explanation is supported by our finding that resource quality also influenced assessment distance at High Harm sites.…”
Section: Discussionmentioning
confidence: 99%
“…Female western grey kangaroos foraged in very open habitats with high grass cover, whereas males foraged in a broader set of habitats that offered a mix of grass and sedges, consistent with the predictions of the forage‐ selection hypothesis for sexual segregation (Clutton‐Brock et al ). It is possible that female foraging decisions were influenced by their reproductive activity (Cripps et al ), as all females had large dependent young during our study. While neither sex used foraging habitats with access to browse, it is likely that females used habitats with higher‐quality resources than males (as previously reported for this species elsewhere, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The energetic costs of lactation are highest for female eastern grey kangaroos when their young are at the LPY and early YAF stages. Females with high lactation demands spent more time feeding and had higher bite rates than non-reproductive females at Serendip Sanctuary, Victoria (Cripps et al 2011). At a different site in Victoria, found that females with a LPY or YAF were significantly more likely to be observed feeding than were females with smaller or without pouch-young.…”
Section: Discussionmentioning
confidence: 87%